ANALISIS EFEKTIVITAS PROGRAM TEKNOLOGI APLIKASI E-RETRIBUSI PASAR (TAPE PASAR) DI KOTA SURAKARTA - Aldy Zulian Saputra; Ida Hayu Dwimawanti; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Teknologi Aplikasi E-Retribusi Pasar (TAPE Pasar) is a program launched by the Surakarta City Trade Office to collect market retribution digitally. This program is expected to increase the value of fees, as well as maximize local revenues through market fees. TAPE Pasar at the Surakarta City Trade Office always needs to be analyzed to assess how effective the program is for users. It is known that the obstacle in this program is that there is a gap between the amount of regional income and the amount of regional fees originating from market fees. This study aims to analyze the effectiveness of the TAPE Pasar program in Surakarta City along with the supporting and inhibiting factors that occur in it. The theory used by researchers is the theory of effectiveness according to Nakamura and Smallwood and the theory that influences effectiveness according to Shabbir Cheema and Rondinelli. This research method is descriptive qualitative with data collection techniques, namely observation, interviews, and documentation. The results of this study reveal that the presence of Pasar Tapes in Surakarta City has not been effective. Factors hindering the effectiveness of this program are that there are still errors in the e-Retribution system which impede payment and there are also elderly traders who do not understand technology so they forget to pay fees. The suggestion from this study is that it is necessary to carry out routine maintenance of the e-Retribution system and the Surakarta Trade Office is expected to conduct training and comprehensive outreach to traders who do not understand technology.